Isatuximab, Bortezomib, Lenalidomide, and Dexamethasone for multiple myeloma - Facon, Thierry; Dimopoulos, Meletios-Athanasios; Leleu, Xavier P.; Beksac, Meral; Pour, Ludek; Hájek, Roman; Liu, Zhuogang; Minarik, Jiri; Moreau, Philippe; Romejko-Jarosinska, Joanna; Spicka, Ivan; Vorobyev, Vladimir I.; et al. (The New England journal of medicine, 2024)
More patients treated with isatuximab, bortezomib, lenalidomide, and dexamethasone had improved progression-free survival and had a complete or better response than those treated with VRd alone.